2023
DOI: 10.1007/s10862-023-10052-w
|View full text |Cite
|
Sign up to set email alerts
|

The Existential Nihilism Scale (ENS): Theory, Development, and Psychometric Evaluation

Abstract: Existential nihilism is a meaning-related worldview characterized by a rejection of the existence of meaning in life and a belief in the futility of trying to ameliorate this absence. Despite the rich but often ambiguous philosophical and cultural history of existential nihilism, its impact on mental health and society remains largely unknown due to a gap in the scientific measurement literature. To address this gap, an 8-item scale measuring the proposed construct was rigorously developed and tested in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…They found that there was a strong negative relationship between existential nihilism and meaning in life. Additionally, high existential nihilism is associated with higher levels of depression and negative affect, and lower levels of life satisfaction, positive affect, and search for meaning (Forsythe and Mongrain, 2023). Their findings support our hypothesis that a deep sense of meaning and existential wellbeing is important for mental health.…”
Section: What Is the Meaning Of Suffering?supporting
confidence: 79%
“…They found that there was a strong negative relationship between existential nihilism and meaning in life. Additionally, high existential nihilism is associated with higher levels of depression and negative affect, and lower levels of life satisfaction, positive affect, and search for meaning (Forsythe and Mongrain, 2023). Their findings support our hypothesis that a deep sense of meaning and existential wellbeing is important for mental health.…”
Section: What Is the Meaning Of Suffering?supporting
confidence: 79%
“…Second, to accommodate the meaning of suffering, individuals may shift their global meaning beliefs in a manner that makes negativity the predominant feature (Park et al, 2012;Gerrish et al, 2014;Gerrish and Bailey, 2020), as in the adoption of cynicism or existential nihilism. Such negative belief orientations are associated with poor well-being outcomes ranging from depressive and anxiety symptoms to suicidal ideation (Nierenberg et al, 1996;Dangel et al, 2018;Forsythe, 2021). Thus, the threat of failure to comprehend the meaning of a suffering event, as well as the potential negative global meaning one might derive, comprise a dimension of suffering that demands cognitive pathways of resolution.…”
Section: Effects Of Self-transcendent Cognition On Sufferingmentioning
confidence: 99%
“…Moreover, such selftranscendent systems of global meaning may likewise successfully incorporate the suffering event-the prospect of death linked to "destruction" in the given example-into a perspective that also emphasizes positive features such as "creation, " thereby accounting for negativity in existence without sacrificing the positive. In contrast, cynicism or nihilism also do provide explanations for suffering, but they do not allow for the inclusion of such positivity and thereby lead to their associated negative well-being outcomes (Dangel et al, 2018;Forsythe, 2021). In providing an orientation of global meaning with a larger perspective and a focus on superordinate values, self-transcendent cognition may thus help resolve both the struggle to formulate acceptable meaning of suffering as well as the potential for maladaptive interpretations.…”
Section: Effects Of Self-transcendent Cognition On Sufferingmentioning
confidence: 99%